Decontamination Procedures For Microbially Contaminated Local Starches - lgwilo, C.; Akpan, U. E.; Alo, B.; Nasipuri, R.; Rabin, O. (The Nigerian Journal of Pharmacy, 1993)
Corn and cassava starches, isolated from local corn grains and cassava tubers and predried to a moisture content of less than 2.0% were exposed to microbial contamination. These contaminated starches were then exposed to various sterilization processes, which include dry heat, and ethylene oxide gas at speciﬁc conditions, for different time periods. These samples were subsequently subjected to U.S.P. (1935) sterility and gross contamination tests from the various results, sterilization by ethylene oxide gas appeared to be the most effective method in reducing bacterial count, followed by the dry heat method. (Preview the download for more on the abstract.)